A Generic Closed‐Loop Contaminant Treatment System Package for MODFLOW 6. Issue 1 (19th August 2022) - White, Jeremy T.; Ewing, John E.; Ruskauff, Greg; Rashid, Helal
Abstract: We present a contaminant treatment system (CTS) package for MODFLOW 6 that facilitates the simulation of pump‐and‐treat systems for groundwater remediation. Using the "nonintrusive" MODFLOW 6 application programming interface (API) capability, the CTS package can balance flows between extraction and injection wells within the outer flow solution loop and applies blended concentration/mass treatment efficiency within the outer transport solution loop. The former can be important when the requested extraction rate cannot be satisfied by the current simulated groundwater system conditions, while the latter can be important for simulating incomplete/imperfect treatment schemes. Furthermore, the CTS package allows users to temporally vary all aspects of a simulated CTS system, including the configuration and location of injection and extraction wells, and the CTS efficiency. This flexibility combined with the API‐based implementation provide a generic and general CTS package that can be applied across the wide range of MODFLOW 6 simulation options and that evolves in step with MODFLOW 6 code modifications and advancements without needing to update the CTS package itself.